2019
DOI: 10.1111/inr.12563
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and ethics violations: Nurses’ responses to hypothetical cases

Abstract: Aim This study aimed to evaluate nurses’ ability to evaluate ethical violations to hypothetical case studies involving social media use. Background Inappropriate use of social media necessitates health institutes, academic institutes, nurses and educators to consider occupational ethical principles while creating a  policy and guide on the usage of social media. Method The data were collected confidentially from the nurses working at a university hospital in Turkey, using the Personal Information Form and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Recommendations to health professionals to avoid violation of ethical principles and norms through their use of social media (e.g. Demiray et al 2020) have been established in several countries and institutions. Therefore, a debate regarding the possible implications for nurses who are not allowed to express their needs inside the organization, and who are also forbidden to express concerns via social media or other outlets, should be opened when the issues affect public health.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations to health professionals to avoid violation of ethical principles and norms through their use of social media (e.g. Demiray et al 2020) have been established in several countries and institutions. Therefore, a debate regarding the possible implications for nurses who are not allowed to express their needs inside the organization, and who are also forbidden to express concerns via social media or other outlets, should be opened when the issues affect public health.…”
Section: Discussionmentioning
confidence: 99%
“…Not all providers were aware of the dangers of infringing privacy when using social media as Alshakh et al, found in their survey [61]. Similarly, when exposed to cases with privacy breaches, only nurses with higher education including more elaborate as well as more recent ethics training could identify the threats [62].…”
Section: Articlementioning
confidence: 90%
“…Alshakhs et al [61] Bittner et al [66] Bopp et al [63] Brisson et al [33] Chandawarkar et al [69] Demiray et al [62] Estrada-Hernandez and Bahr [60] Geis et al [67] Ho and Quick [57] Jaremko et al [70] Le Barge and Broom [65] Modell et al [59] Reamer [71] Robillard et al [68] Sussman and DeJong [72] Zimba et al [64]…”
Section: Articlementioning
confidence: 99%